Candi Merak: Antara Peninggalan, Pelestarian, dan Harapan (Sebuah Kajian Filologi) - Susena, Danang; Budiyono, Sri (Sutasoma : Jurnal Sastra Jawa, 2021)
Many folk stories are recorded in book form (manuscripts), but some are still in verbal form (oral stories). To facilitate and increase the provision of data sources on local wisdom in the form of books (manuscripts), it is necessary to carry out an inventory of these texts, one of which is an inventory of the legend of the origin of the name Merak Temple which is located in Karangnongko District, Klaten Regency. Departing from the above statement, this study aims to inventory the folklore about the origin of the name Merak Temple which is located in Candi Dukuh, Karangnongko Village, Karangnongko District, Klaten Regency. This research uses qualitative methods, namely research conducted to understand what is experienced by research subjects holistically, descriptively in the form of words and language, in a natural and scientific context. This method is used to analyze the legendary text of the origin of the name of the Merak temple. This research is a folklore research. Basically, this research begins with an inventory of the legendary stories in the form of manuscripts. Furthermore, the legend manuscript becomes the object of research, from reading the text of the legend of the origin of the peacock temple, it can be described the data which is the source of local wisdom in it, namely pamali (taboo / taboo) and recommendations contained in the text. The results showed that pamali or taboo is an expression of prohibition that arises in connection with the existence of the Merak Temple in Pura Karangnongko Hamlet. Pamali is trusted and believed by the hamlet community around Candi Merak as a rule that must be obeyed. Pamali found regarding the existence of the Merak Temple in the dukuh community was the prohibition of acting immoral or saying dirty, disrespectful words, spitting, throwing garbage (feces) around the temple. If the prohibition is violated, it will result in the person concerned being injured / unluck. Keywords: merak temple, local wisdom, folklor, pamali